Penggunaan Permainan Tic Tac Toe dalam Meningkatkan Kompetensi Pedagogik Mahasiswa PAI UIN Malang - Arifa, Laily Nur (J-PAI: Jurnal Pendidikan Agama Islam, 2022)
Education in the 21st century demands developing strong pedagogical skills, including critical thinking, problem-solving, and communication abilities. This study explores using the Tic Tac Toe game as a learning method to enhance the pedagogical competence of Islamic Education students at UIN Malang. This research was conducted using an experimental method with the design of a Single Subject Experiment. This research demonstrates that this game-based intervention positively impacts students' pedagogical competence. The results show a significant average score increase from the baseline to the intervention phase, indicating that the Tic Tac Toe game can facilitate active learning, motivate participation, and assist in developing critical and strategic thinking skills. Although these results highlight the potential of games as effective learning tools, further research is needed to understand how and why this game impacts students' pedagogical competence in various contexts and disciplines